Strategi Pengembangan Desa di Daerah Perbatasan Berdasarkan Potensi Pertanian Lokal: Studi Kasus di Desa Nanga Bayan, Kabupaten Sintang Sebagai Daerah Perbatasan Indonesia-Malaysia - Antonius, Antonius; Nikodimus, Nikodimus; Redin, Redin; Salim, Kartika Agus; Kaja, Kaja; Mangardi, Mangardi; Paulus, Paulus; Marjun, Agustinus; Kurnianto, Alexander Andi; Setiawan, Hendra (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
The border area is the front porch for a country that represents the development of the country. This study aims to identify the potential of local village agriculture that supports family economic strengthening, analyze the economic value of local village potential, formulate a strategy development of Nanga Bayan village. This research was conducted in Nanga Bayan Village, Ketungau Hulu District, Sintang Regency, West Kalimantan Province, in April-September 2023. This research used triangulation method and data are collected through semi-structured interviews, FGDs, and observations. The data were analyzed using descriptive qualitative analysis. SWOT analysis used to formulate the development strategy of Indonesia-Malaysia’s border area. The results showed that the local potential in Nanga Bayan Village as a border area are local agricultural products based on traditional fields, local fruit; traditional weaving and clean water sources. The economic commodities of the people in Nanga Bayan Village are attracting Malaysian. However, transactions that occur are not through official cross-border. The development strategy of the Indonesia-Malaysia Border Village is to develop commodities that are attract Malaysian market. In addition, it is hoped that the plan to build cross-border posts in this area can increase the official buying and selling of goods at the border.